KOMUNIKASI DIPONEGORO DAN POST-TRUTH ERA PROPAGANDA KLASIK JAWA - Firmantoro, Verdy; Sujoko, Anang; Antoni, Antoni (Jurnal Nomosleca, 2018)
This study is manifestation of a non-Western perspective communication research. The dominance of western perspective in communication studies encourages the development of contextual non-Western communication with the source from historical and socio-cultural as a grounded alternative perspective. This study is aims to read the era by examining the historical traces of Prince Diponegoro and post-truth practices that occurred during the Javanese classical propaganda era around the late 18th century and early 19th century. This study uses historiography method through literature review of historical texts related to Prince Diponegoro and social history at that time. The results of this study reveal the fields of production of reality that are influenced by the colonial culture and the practice of de-islamization that separates the local wisdom of the Palace and tradition of the Javanese society. The intersection of Prince Diponegoro’s resistance to the amoral values implies the creation of a negative construction of Prince Diponegoro as a rebel figure who only wants to gain power in the land of Java. The clarity of reading historical reality is important in order to avoid a factual twist as a whole of civilization. Keywords: Pangeran Diponegoro, Post-Truth, Colonial Communication, non-Western Perspective, IdentityDOI : https://doi.org/10.26905/nomosleca.v4i1.1974